Analysis of English Learning Activities for Medical Students - Islam, Raudhatul (Universitas Islam Lamongan, 2024)
English for Specific Purposes is needed by people who work in specific fields such as medicine, military, business, and other fields. This research aims to analyze the ESP learning method applied by a lecturer at Hafsawaty Zainul Hasan University. This research method is based on a descriptive method concerning a qualitative approach. This research is proposed to focus on teaching English to medical students. The result of this research is that most students have difficulty understanding English learning due to the lack of supporting media and non-innovative learning. Therefore, in teaching English, the lecturer not only tends to the material in the module but also recommends that students watch YouTube channels relevant to the material being taught or use applications such as Quizizz, which support the learning process. The ESP lecturers stated that ESP learning for students (medical students) is quite well developed but requires a little auxiliary media to make it easier for students to understand English or ESP lessons. As in the current era, a teacher must apply innovative and creative learning methods so students do not experience monotonous learning. Students often feel bored and are not interested in the learning system, which tends to be monotonous. Therefore, lecturers use technology as a teaching medium to support teaching and learning.